Next-Generation Sequencing Technology Combined With Multiplex Polymerase Chain Reaction as a Powerful Detection and Semiquantitative Method for Herpes Simplex Virus Type 1 in Adult Encephalitis: A Case Report - Chen, Weibi; Wu, Yingfeng; Zhang, Yan (Frontiers in Medicine, 2022)
Background Traditional testing for specific microbes or categories of central nervous system (CNS) infectious diseases is often limited in sensitivity and timeliness. However, failure to initiate a timely etiological diagnosis and corresponding treatment in patients with neurologic infections contribute to poor outcomes. Case Summary A 58 year-old male presented acutely with fever, abnormal mental behavior, seizures and decreased consciousness. Brain magnetic resonance imaging (MRI) showed an abnormal FLAIR/T2 signal mainly in the left thalamus, temporal lobe, insular lobe, and bilateral hippocampus. To identify the pathogen, the cerebrospinal fluid (CSF) sample of the patient was used for metagenomic next-generation sequencing (mNGS) analysis and multiplex polymerase chain reaction (mPCR). The results showed 188 herpes simplex virus (HSV-1)-specific sequences. After acyclovir and foscarnet sodium treatment, the ratio of HSV-1/internal reference reads decreased from 813/493 to 695/1961, which coincided with clinical remission. Conclusion This study indicates that mNGS combined with mPCR may be an effective method for etiological diagnostic and dynamic clinical surveillance for HSV-1 encephalitis.